Utilization of Biomass as a Carbon Source for The Synthesis of Graphene as a Sustainable Materials Innovation - Dina Rahmawati; Melda Taspika; Nur Afifah Zen (Sustainability (STPP) Theory, Practice and Policy, 2021)
One of the alternative ways to reduce the use of fossil fuels is the advancement of energy storage devices and energy conversion devices for renewable energy. The electrode is an essential part of its electrochemical performance in energy storage. The specific surface area of the electrode will affect the energy density, lifetime, charging, and discharging of the energy storage devices. Graphene has been widely used for energy storage, such as batteries and supercapacitors. Generally, graphene is synthesized from graphite as a carbon source which some researchers have reported. However, they are still fighting against simple synthesis methods, low-cost raw materials, eco-friendly co-product, and large-scale production. Therefore, advanced research is required to bring graphene from laboratory-scale projects to industry. One of the best solutions is biomass as a raw material to replace graphite in synthesizing graphene. In this review, some methods for synthesizing graphene from biomass will explain briefly, following with their strength and weakness.